2008
DOI: 10.2134/jeq2007.0442
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Plant Responses from Land Application of Saline–Sodic Waters: Implications of Management

Abstract: Land application of co-produced waters from coalbed natural gas (CBNG) wells is one management option used in the Powder River Basin (PRB) of Wyoming and Montana. Unfortunately, the co-produced CBNG waters may be saline and/or sodic. The objective of this study was to examine the effects of irrigation with CBNG waters on soils and plants in the PRB. Soil properties and vegetation responses resulting from 1 to 4 yr of saline-sodic water (electrical conductivity [EC], 1.6-4.8 dS m(-1); sodium adsorption ratio [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Furthermore, SAR values greater than 13 pose a risk to the soil ecosystem [94]. Typical treatments to mitigate the effects of saline-sodic irrigation water include the addition of gypsum and elemental sulphur [21,98].…”
Section: Problem Definitionmentioning
confidence: 99%
“…Furthermore, SAR values greater than 13 pose a risk to the soil ecosystem [94]. Typical treatments to mitigate the effects of saline-sodic irrigation water include the addition of gypsum and elemental sulphur [21,98].…”
Section: Problem Definitionmentioning
confidence: 99%
“…The continuously watered plants in both studies decreased forage yield due to water logging. Vance et al (2008) studied the soil physical parameters as well as plant diversity on range and crop land being irrigated with produced water. Sulfur burners have been used to decrease the pH of the water; however this did not decrease the amount of total dissolved solids, salts, or Na content of the water.…”
Section: Esp =mentioning
confidence: 99%
“…A recent boom in coal-bed methane production in the Powder River Basin of northeastern Wyoming has created large quantities of produced water from well sites; with total water production as of 11 February 2014 at 7.7 bcf (Wyoming Oil and Gas Conservation Commission, 2014). When used for irrigation, due to high sodicity and salinity, the water often has deleterious effects to the soil that must be managed (Vance et al, 2008). Produced water's effects on plants are less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Vance et al (2008) suggested that a loss of grassland community diversity at Na-affected wastewater land application sites in semiarid Wyoming may limit the ultimate restorative potential of the land. Further research is needed to elucidate the edaphic changes resulting from effluent land application that may, in turn, regulate species productivity and diversity in semiarid ecosystems.…”
Section: Ecological Considerationsmentioning
confidence: 99%